2014
DOI: 10.1016/j.transproceed.2014.05.075
|View full text |Cite
|
Sign up to set email alerts
|

Improved Coating of Pancreatic Islets With Regulatory T cells to Create Local Immunosuppression by Using the Biotin-polyethylene Glycol-succinimidyl Valeric Acid Ester Molecule

Abstract: Background We showed that T regulatory (Treg) cells can be attached to the surface of pancreatic islets providing local immunoprotection. Further optimization of the method can improve coating efficiency, which may prolong graft survival. In this study, we compared the effectiveness of two different molecules used for binding of the Tregs to the surface of pancreatic islets. Our aim was to increase the number of Treg cells attached to islets without compromising islets viability and function. Methods Cell su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Here, we chose the acryl‐poly(ethylene‐glycol)‐succinimidyl‐valerate (APSV) photolinker as it is highly soluble in water and displays improved stability to hydrolysis compared to N ‐hydroxy‐succinimide (NHS) counterparts [ 33 ] making it overall more reliable.…”
Section: Figuresupporting
confidence: 87%
“…Here, we chose the acryl‐poly(ethylene‐glycol)‐succinimidyl‐valerate (APSV) photolinker as it is highly soluble in water and displays improved stability to hydrolysis compared to N ‐hydroxy‐succinimide (NHS) counterparts [ 33 ] making it overall more reliable.…”
Section: Figuresupporting
confidence: 87%
“…Furthermore, insulinotropic peptides, such as glucagon‐like peptide‐1 (GLP‐1), exendin‐4 (Ex‐4), or insulin‐like growth factor‐1 (IGF‐1), as well as proangiogenic factors and cells such as VEGF, platelet‐derived growth factor (PDGF), and endothelial cells (ECs), have been combined with these scaffolds and islets, in both in vitro (Kizilel et al, ; Lin & Anseth, ) and in vivo approaches (Brady et al, ; Farina et al, ; Hlavaty et al, ; Y. Li et al, ; Linn et al, ; Phelps, Headen, Taylor, Thulé, & García, ; Phelps, Templeman, Thulé & García, ), showing significant improvements in insulin secretion, islet survival, and engraftment. In other studies, immunosuppressive drugs (Haque, Jeong, & Byun, ; Pinto et al, ) or even immunomodulatory cells, such as regulatory T cells (Treg; Graham et al, ) or mesenchymal stem cells (MSCs; Borg et al, ; Gołąb et al, ; Marek et al, ), were combined with synthetic materials and used in vitro and in vivo to enhance their immunoprotective functions and subsequently prevent the immune reaction against nonautologous islets. Moreover, with the aim of “functionalizing” these synthetic scaffolds, that is, increasing their biocompatibility, they have been coupled with bioactive agents that increase the hydrophilicity of their surfaces (Liu, Holzwarth, & Ma, ).…”
Section: Tissue Engineering In Islet Transplantationmentioning
confidence: 99%
“…In 2006, Krol et al demonstrated that islets can be nanoencapsulated through a layer-by-layer approach using alternating layers of either polyallylamine hydrochloride or poly-diallyldimethylammonium chloride as polycations and polystyrene sulfonate as a polyanion [177]. Subsequent studies improved the layer-by-layer coating by using a biotin-PEG peptide conjugated with streptavidin in the PEG coating [178,179]. Nanoencapsulation of islets using alternate layers of phosphorylcholine-derived polysaccharides and algi-nate normalized blood sugar levels and reversed hyperglycemia in diabetic mice in an allotransplantation setting [180].…”
Section: Layer-by-layer Coatingmentioning
confidence: 99%